2020
DOI: 10.1186/s40814-019-0548-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic LED light versus static LED light for depressed inpatients: results from a randomized feasibility trial

Abstract: Background: Retrospective studies conducted in psychiatric wards have indicated a shorter duration of stay for depressed inpatients in bright compared to dim daylight-exposed rooms, pointing to a possible antidepressant effect of daylight conditions. Dynamic LED lighting, aiming to mimic daylight conditions, are currently been installed in several hospitals, but their feasibility is poorly investigated. Methods: To investigate the feasibility of these systems, we developed and installed a LED-lighting system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Suicidal ideation levels in the present study were lower than those reported among individuals with likely MDD (based on the PHQ-9) in the SIDAS validation manuscript (Van Spijker et al, 2014), as well as those previously described in inpatient (Volf et al, 2020) and outpatient (Halford et al, 2021) clinical trials for the treatment of MDD. These relatively low levels of suicidal ideation may be attributable to several of the present study's exclusion criteria, including exclusion of individuals with a history of serious suicide attempts requiring hospitalisation and several clinical presentations characterized by elevated suicidal ideation (e.g., borderline personality disorder, psychotic disorder, drug or alcohol dependence, and a history of mania).…”
Section: Improvements In Mental Health Via Reductions In Experiential...supporting
confidence: 83%
“…Suicidal ideation levels in the present study were lower than those reported among individuals with likely MDD (based on the PHQ-9) in the SIDAS validation manuscript (Van Spijker et al, 2014), as well as those previously described in inpatient (Volf et al, 2020) and outpatient (Halford et al, 2021) clinical trials for the treatment of MDD. These relatively low levels of suicidal ideation may be attributable to several of the present study's exclusion criteria, including exclusion of individuals with a history of serious suicide attempts requiring hospitalisation and several clinical presentations characterized by elevated suicidal ideation (e.g., borderline personality disorder, psychotic disorder, drug or alcohol dependence, and a history of mania).…”
Section: Improvements In Mental Health Via Reductions In Experiential...supporting
confidence: 83%
“…The heart rate, i.e., respiratory rate parameter, was taken as the mean value for one minute during environmental stimulation. Independent t-test was used to analyze the degree of difference in physiological fluctuations brought about by the dynamic and static lighting environment [5] .…”
Section: Resultsmentioning
confidence: 99%
“…6a); (ii) high irradiance that might be used for testing aging processes of materials [41,42] (Fig. 6b); (iii) full bright sunlight on a sunny and cloud free situations [43,44,45] (Fig. 6c); (iv) the spectral irradiance environment of understory plants within a tree (birch) canopy [46,47,48] (Fig.…”
Section: Simulation Of the Spectral Irradiance Of Sunlight In The Diumentioning
confidence: 99%